SARCASM AND IRONY IN ENGLISH AND UZBEK LITERATURE - Umaraliyeva Munojotxon Mashrabovna; Anvarova Mushtariybonu Mirzohidjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: The article presents the utilization of irony and sarcasm, as well as some examples of them in Uzbek and English literary works. Irony is a methodological tool; as if you approved or gave an aggreement, rejection, sarcastic laughter. In irony, a word or expression acquires in speech the opposite of its original meaning, even the content that refutes it. Philosophers, literary critics, and linguists study this subject. The term that is called ironology is also a field of science and study of irony.